NV: An Intermediate Language for Verification of Network Control Planes - Giannarakis, Nick; Loehr, Devon; Beckett, Ryan; Walker, David (Programming Language Design and Implementation, 2020)
Network misconfiguration has caused a raft of high-profile outages over the past decade, spurring researchers to develop a variety of network analysis and verification tools. Unfortunately, developing and maintaining such tools is an enormous challenge due to the complexity of network configuration languages. Inspired by work on intermediate languages for verification such as Boogie and Why3, we develop NV, an intermediate language for verification of network control planes. NV carefully walks the line between expressiveness and tractability, making it possible to build models for a practical subset of real protocols and their configurations, and also facilitate rapid development of tools that outperform state-of-the-art simulators (seconds vs minutes) and verifiers (often 10x faster). Furthermore, we show that it is possible to develop novel analyses just by writing new NV programs. In particular, we implement a new fault-tolerance analysis that scales to far larger networks than existing tools.